Application of diatomite for sorption of Pb, Cu, Cd and Zn from aqueous solutions: kinetic, thermodynamic studies and application of response surface methodology (RSM). (27th December 2020) - Piri, Marziyeh; Sepehr, Ebrahim; Samadi, Abbas; Farhadi, Khalil; Alizadeh, Mohammad
Abstract: Contamination of water and soil with toxic metals is a serious environmental issue. To study the Pb, Cu, Cd, and Zn sorption behavior by diatomite, batch experiments were carried out with increasing levels of initial concentration (0–200 mg/L) under different contact times (0–360 min) and temperatures (283, 293, 303, and 313 K). The effects of concentration (0–200 mg/L), pH (3–6), and ionic strength (0.01–0.06 mol/L) on the sorption were modeled using response surface methodology (RSM). Results showed that adsorption data were well‐fitted by the Langmuir equation. The sorption of metals intensified by increasing initial concentration and pH but ionic strength had inverse effect. High value for R 2 (0.99) and adjusted R 2 (0.99) showed that the removal of ions can be described by response surface method. One‐way ANOVA showed ( p ‐value < 0.0001) that quadratic model is the best model for determining the interaction of variables. The values of the sorption energy parameter from Dubinin–Radushkevich model ( E  < 8 kJ K −1  mol −1 ) and negative values of ∆ G showed that the sorption of the metals was physical and spontaneous. The positive values of enthalpy (Δ H ) indicated that the sorption reaction of metals was endothermic at 283–313 K. Practitioner points: Applications of diatomite increased the sorption of Pb, Cd, Zn, and Cu from aqueous solutions. Diatomite, as low‐cost adsorbent, had significant potential to sorption of ions. The sorption of heavy metals by adsorbent intensified by increasing initial concentration and pH but ionic strength had inverse effect. High value for R 2 (0.99) and adj‐ R 2 (0.99) showed that removal of metals can be described by response surface method (RSM) and the initial concentration of metal was the most significant factor. Abstract : Removal of heavy metals by diatomite.